Pendampingan Pembelajaran Ghorib Walmuskilat bagi Pembina Taman Pendidikan al-Qur’an (TPQ) - Nabil, Sulthan; Cholis Agus Santoso, Nur; Malik , Muhammad (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
Education is an important factor in the advancement of a people to eliminate ignorance. One of the main keys to eliminating ignorance is to read more, especially if it is related to the Qur'an, a holy book of Muslims who should not be mistaken to take advantage of it. Therefore, this is where the importance of a teacher to accompany learning activities related to the Qur'an. At TPQ Al Muttaqiin, there is very little litration of learning or knowledge related to the Qur'an because there are no competent teachers to teach. This is where we finally promote learning that is suitable for them, namely by learning Ghorib Walmuskilat with the ABCD (Asset Based Community Development) approach used to utilize the potential of the community in implementing the program. Through these steps, it is hoped that the existence of mentors in the hamlet can increase understanding, broaden horizons, and have a positive impact on local religious activities.